2018
DOI: 10.1002/hep.30125
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐Reported Outcomes and the Economic Effects of Nonalcoholic Fatty Liver Disease and Nonalcoholic Steatohepatitis: The Value Proposition

Abstract: Nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) can progress to cirrhosis, hepatocellular carcinoma (HCC), death, or liver transplantation. NASH has also been associated with impaired health-related quality of life and poses a significant economic burden. Due to the negative clinical and patient-reported outcomes and economic burden of NAFLD, it is necessary to review this disease through the lens of value-based care, in which value is proportional to clinical and quality outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 60 publications
0
40
0
Order By: Relevance
“…Bariatric surgery and newer endoscopic procedures can only be considered for morbidly obese individuals who are candidates for these interventions. [118][119][120][121][122] In addition, we must also consider the social determinants of health when developing strategies to combat the development of NAFLD. In this context, social determinants are broadly defined as the external factors which can separate the health status of one area from another.…”
Section: Key Pointmentioning
confidence: 99%
“…Bariatric surgery and newer endoscopic procedures can only be considered for morbidly obese individuals who are candidates for these interventions. [118][119][120][121][122] In addition, we must also consider the social determinants of health when developing strategies to combat the development of NAFLD. In this context, social determinants are broadly defined as the external factors which can separate the health status of one area from another.…”
Section: Key Pointmentioning
confidence: 99%
“…Lifestyle and physical health in early life can be long-term determinants of a muscle strength decline [9]. Several previous reports highlighted the importance of improving QOL in patients with CLDs [10][11][12][13][14]. We previously demonstrated that grip strength (GS) was closely linked to health-related QOL as assessed by the 36-Item Short-Form Health Survey (SF36) in patients with CLDs [15].…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the burden of NAFLD is also seen in economic modeling and population‐based studies . NAFLD‐associated costs over the next 10 years are projected to be an estimated $1.005 trillion in the United States and €334 billion in Europe .…”
mentioning
confidence: 99%
“…NAFLD‐associated costs over the next 10 years are projected to be an estimated $1.005 trillion in the United States and €334 billion in Europe . Patients with NAFLD also report a decrease in their health‐related quality of life, especially in the area of physical functioning, which affects their ability to work and perform activities of daily living . Despite the significant burden posed by NAFLD, fully validated noninvasive diagnostic tests are lacking and effective treatment for NASH is limited .…”
mentioning
confidence: 99%